Pengaruh Profitabilitas, Solvabilitas Dan Ukuran Perusahaan Terhadap Audit Delay - Farhana Hasmin (STIEM BONGAYA, 2021)
The impact of profitability, solvency and corporate size against the delay audit of property and real estate firms registered in the Indonesian stock exchange (guided by ibrahim and andi patware).The study suggests that profitability has a significant positive impact on delayed audits, solvability has a significant positive impact on delay audits and company sizes of a significant negative impact on property and real estate audits. At the Indonesian stock exchange.The study suggests that profitability has a significant positive impact on the delay audits, solvency has a significant positive impact on the delay audits and corporate sizes of an unfavorable impact on the delay audits of property and real estate firms in the Indonesian stock exchange.